ЗАРАЖЕННОСТЬ ШИПА (ACIPENSER NUDIVENTRIS) МОНОГЕНИЕЙ DICLYBOTHRIUM ARMATUM В УСЛОВИЯХ УЗВх УЗВ - Ф. Нуржанова; Б. Сатыбаев; А. Дарменова; Б. Ертлеуова; Б. Кадралиева; Г. Абсатиров; Б. Сидихов (Animal Health and Biosafety, 2026)
In recent years, the cultivation of the ship sturgeon has been increasingly implemented in commercial aquaculture facilities operating RAS. Among the parasitic diseases affecting sturgeons, monogenean infections are of particular concern because these parasites possess a direct life cycle, facilitating their rapid transmission under intensive farming conditions. One of the most widespread and pathogenic species is Diclybothrium armatum, a host-specific monogenean parasite of sturgeons, including the ship sturgeon. The study was conducted at a commercial sturgeon farm operating under RAS conditions. A total of 149 fish were examined during the study period. Parasitological examination was performed using routine clinical and parasitological inspection methods. Monogeneans, Diclybothrium armatum, were detected on the gill arches of the examined fish. Detailed examination of the gill apparatus revealed that a considerable proportion of parasites, which were not visible during the initial visual inspection, were located between the gill filaments. The prevalence of infection reached 34.2%, indicating a relatively high distribution of the parasite within the examined population. The mean intensity of infection was 6.2 ± 0.8 parasites per infected fish. The results demonstrated a pronounced age-related susceptibility of sturgeons to D. armatum infection under RAS conditions. Stocking density was identified as a critical factor influencing the development and spread of diclybothriosis.Assessment of pathological alterations associated with D. armatum parasitism revealed marked structural damage to the gill apparatus. The severity of pathological changes depended on parasite burden, attachment site, and duration of infection. The obtained results indicate that under RAS conditions diclybothriosis caused by Diclybothrium armatum is characterized by continuous circulation of the parasite within the production system. The high prevalence of infection observed in juveniles (57.7%) is consistent with the findings of Kazarnikova (2014), who reported increased susceptibility of young ship sturgeon to diclybothriosis. These findings are in agreement with previous international studies demonstrating the considerable pathogenicity of Diclybothrium armatum in cultured sturgeon species.